Determination of Scale Effects on Mechanical Properties of Berea Sandstone. (9th February 2021) - Li, Hui; Song, Kaoping; Tang, Mingguang; Qin, Ming; Liu, Zhenping; Qu, Ming; Li, Ben; Li, Yan
Abstract : The key rock mechanical parameters are strength, elastic modulus, Poisson's ratio, etc., which are important in reservoir development. The accurate determination of reservoir's mechanical properties is critical to reduce drilling risk and maximize well productivity. Precisely estimating rock mechanical properties is important in drilling and well completion design, as well as crucial for hydraulic fracturing. Rocks are heterogeneous and anisotropic materials. The mechanical properties vary not only with rock types but also with measurement methods, sample geometric dimensions (sample length to diameter ratio and size), and other factors. To investigate sample scale effects on rock mechanical behaviors, unconfined compression tests were conducted on 41 different geometric dimensions of Berea sandstones; unconfined compressive strength (UCS), Young's modulus (E ), Poisson's ratio (υ ), bulk modulus (K ), and shear modulus (G ) were obtained and compared. The results indicate that sample geometry can significantly affect rock mechanical properties: (1) UCS decreases with the increase of length to diameter ratio (LDR), and the UCS standardize factor is between 0.71 and 1.17, which means -30% to +20% variation of UCS with LDR changing from 1 to 6.7. The test results show UCS exhibits positive relationship with sample size. (2) Young's modulus slightly increases with LDR increases, while Poisson's ratio decreases with the increase of LDR. For the tested Berea sandstones, Poisson's ratio standardizing factor is between 0.57 and 1.11. (3) Bulk modulus of Berea sandstone samples decreases with the increase of LDR, while shear modulus increases with LDR increases. Both bulk modulus and shear modulus increase with the increase of sample size. (4) The principal failure modes were analyzed. The failure modes of the tested Berea sandstones are axial splitting and shear failure. Stocky samples (LDR < 2 ) tend to go axial splitting, while slender samples (LDR > 2 ) tend to show shear failure.